2007
DOI: 10.1016/j.brainres.2006.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in estrogen receptor-alpha mRNA in the mouse cortex during development

Abstract: Estrogen plays a critical role in brain development and is responsible for generating sex differences in cognition and emotion. Studies in rodent models have shown high levels of estrogen binding in non-reproductive areas of the brain during development, including the cortex and hippocampus, yet binding is diminished in the same areas of the adult brain. These binding studies demonstrated that estrogen receptors decline in the cortex during development but did not identify which of the two estrogen receptors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 36 publications
9
63
2
Order By: Relevance
“…In rats, ERα mRNA expression was also shown to correlate with the changes in estrogen binding in the hippocampus [56]. Similar changes in ERα mRNA expression during the first three weeks of postnatal life have also recently been shown in the cortex of mice [52]. By the time animals reach adulthood, however, ERα mRNA is expressed at very low levels in the mouse cortex.…”
Section: Regulation Of Estrogen Receptor Mrnamentioning
confidence: 60%
“…In rats, ERα mRNA expression was also shown to correlate with the changes in estrogen binding in the hippocampus [56]. Similar changes in ERα mRNA expression during the first three weeks of postnatal life have also recently been shown in the cortex of mice [52]. By the time animals reach adulthood, however, ERα mRNA is expressed at very low levels in the mouse cortex.…”
Section: Regulation Of Estrogen Receptor Mrnamentioning
confidence: 60%
“…Primer specific concentrations were previously optimized for each gene and result in a single DNA PCR product with no primer-dimer formation (Dubal et al, 1999, Prewitt andWilson, 2007). Each 96 well plate contained a non-template control and each sample was run in triplicate.…”
Section: Real Time Pcrmentioning
confidence: 99%
“…Another study using ERα knockout mice also suggested that in male ERα knockout mice, the absence of ERα did not increase the ischemia-induced damage, but these males were not given estradiol (Sampei et al, 2000). In both male and female rodents, ERα mRNA expression is high in the neonatal cortex, but dramatically decreased to only a few cells in the uninjured adult cortex (Miranda andToran-Allerand, 1992, Prewitt andWilson, 2006). Twenty-four hours after MCAO, however, ERα mRNA and protein are significantly increased in the cortex of female rats and mice (Dubal et al, 1999, Dubal et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that when administered several days before inducing cerebral ischemia, physiological levels of estradiol attenuate brain injury through the suppression of neuronal apoptosis and genomic actions by acting through mechanisms of the classical nuclear estrogen receptors (Liao et al , 2001 ;Prewitt and Wilson , 2007 ;Jia et al , 2009 ;Suzuki et al , 2009 ); this is, however, not the case with acute administration of 17 β -estradiol at the time of injury, as this does not reduce the extent of infarction (Dubal et al , 1998 ;Suzuki et al , 2009 ).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Permanent ischemia leads to severe metabolic impairment in the cerebral cortex, which results in necrosis of many neurons in the region within several hours following injury. Regions surrounding the core of ischemia can be salvaged from apoptosis through the powerful neuroprotective action of 17 β -estradiol (Prewitt and Wilson , 2007 ;Suzuki et al , 2009 ), but the effects of estradiol at the ischemic core are only visible in transient ischemic models. Conclusively, 17 β -estradiol protects the brain through suppression of neuronal apoptosis during the initial 24 hours after injury, in part by suppressing the infl ammatory response, and enhances neurogenesis within the fi rst 96 hours after ischemic stroke (Suzuki et al , 2009 ).…”
Section: Neuroprotectionmentioning
confidence: 99%